2018
DOI: 10.1001/jamapsychiatry.2018.1483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Transcranial Magnetic Stimulation on Treatment-Resistant Major Depression in US Veterans

Abstract: ClinicalTrials.gov Identifier: NCT01191333.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 21 publications
6
121
5
Order By: Relevance
“…Alternately, disease heterogeneity may be related to changes in FC that are challenging to predict at the individual level with current approaches. Others have reported the opposite direction of association with the largest improvements in depression being associated with the largest reductions in FC between sgACC and mDMN (66); however, their patient cohort had comorbid post-traumatic stress disorder, which may respond differently to rTMS of the lDLPFC (67). Further, both Philip et al (66) and our current report found an overall reduction in mean FC between sgACC and DMN in participants with improved depressive symptoms.…”
Section: Discussioncontrasting
confidence: 48%
“…Alternately, disease heterogeneity may be related to changes in FC that are challenging to predict at the individual level with current approaches. Others have reported the opposite direction of association with the largest improvements in depression being associated with the largest reductions in FC between sgACC and mDMN (66); however, their patient cohort had comorbid post-traumatic stress disorder, which may respond differently to rTMS of the lDLPFC (67). Further, both Philip et al (66) and our current report found an overall reduction in mean FC between sgACC and DMN in participants with improved depressive symptoms.…”
Section: Discussioncontrasting
confidence: 48%
“…Electroencephalography might represent a more thorough reflection of cortical excitability than motor evoked potentials (MEP) (Rocchi et al, 2018). Consistent with this variability in healthy subjects, another study observed that less than half of patients with major depression could achieve symptom remission after days of rTMS treatment (Yesavage et al, 2018). Here, we defined the after-effects induced by days of rTMS as long-term effect (LTE).…”
Section: Introductionmentioning
confidence: 79%
“…Although rTMS protocols may stably increase or decrease the neural excitability at the group level, high variability of the after-effect was also reported across subjects Yesavage et al, 2018). In these studies, MEP is frequently used as a readout measure.…”
Section: Individual Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been four large, multicenter, randomized controlled trials on the antidepressant effect of high‐frequency prefrontal rTMS (for a total of 782 subjects studied) . Of these (291 participants), two revealed negative results with no difference in the responder rates of the real and the sham treatment groups (differently from the others, one of these studies involved adjunctive TMS and medications starting simultaneously rather than TMS as the primary treatment or monotherapy). The other two trials showed positive results, that is, 3 to 6 weeks of daily (weekdays only) high‐frequency rTMS over the left DLPFC improved clinical outcomes significantly more than placebo .…”
Section: Why Rtms Might Be Used As a Therapeutic Toolmentioning
confidence: 99%